Significance assessment and cultural heritage management in Ambon Bay, Maluku: Kajian nilai penting dan pengelolaan warisan budaya di Teluk Ambon, Provinsi Maluku - Sugiyanto, Bambang; Surbakti, Karyamantha (Berkala Arkeologi, 2023)
The study about the significance value and cultural heritage management in Ambon Bay was carried out related to the planning for development of an Integrated Port by the Ambon City Government. The development plan aim to manage the natural and environmental resources in Ambon Bay and its surroundings, including several cultural heritages that are full of archaeological and historical value. Research regarding the significant value of cultural heritage in Ambon Bay using field observations is supported by literature studies regarding the history and sustainable management of cultural heritage. The research aims to review the significant value of cultural heritage in Ambon Bay and reinterpret the concepts and methods of managing cultural heritage in this area so that it remains sustainable and can be utilized on a wider scale by various stakeholders and other communities. The result obtained from this research is establishing effective collaboration among stakeholders as a strategy is needed to protect all possibilities that result in the loss of cultural heritage value in Ambon Bay due to development that is indifference to the authenticity of ancient remains.